Efeito da densidade das sementes sobre o teor de proteína e lisina do endosperma e do germe, em milho - Cunha Filho , Edgar; Anderson, John C; Silva , Jairo; Silva , Tácito; de Almeida Filho, José (Revista Ceres, 2025)
The objettive of this experiment was to study the influence of kernel density on protein and lysine content of the endo- sperm and germ in the S, generation of opaque-2 maize whose endosperm presented translucent spots.